Aetiology of running-related gastrointestinal dysfunction. How far is the finishing line? - Gil, S. M.; Yazaki, E.; Evans, D. F. (Sports Medicine, 1998)
30 to 65% of long distance runners experience gastrointestinal (GI) symptoms related to exercise. Several hypotheses have been postulated; however, the aetiology and pathophysiology are far from clear. The mechanical effect of running on the viscera must be involved in the development of GI symptoms in this sport. Reduction of splanchnic blood flow due to visceral vasoconstriction is another widely supported theory; nevertheless, it does not explain many of the clinical findings. Examination of the GI tract during exercise is a difficult task, and measurements of both orocaecal and whole-gut transit time have shown equivocal results. GI hormones, and especially prostaglandins, may be of crucial importance for the production of symptoms. Intestinal absorption, secretion and permeability may also be altered during exercise, provoking intestinal dysfunction. Factors such as stress, diet, dehydration, infections and other factors need to be analysed in order to present a global view of the hypotheses regarding the aetiology of this common and often overlooked problem.